Slipperation of thermal and flow speed impacts on natural convective two-phase nanofluid model across Riga surface: Computational scrutinization. (June 2022) - Patil, Vishwambhar S.; Shamshuddin, MD.; Ramesh, K.; Rajput, Govind R.
Abstract: The rich arena of multi-physical transport phenomena inherent to Riga plate sensor flows has stimulated considerable interest in mathematical modelling, which provides an important compliment to experimental testing. Numerical studies are reported Buongiorno modelled nanofluid flow considered over porous elongated Riga plate surface kept with influence of heat dissipation and non-uniform heat source/sink subjected to velocity and thermal slip conditions. A two-dimensional (2D) mathematical model is developed based on a Buongiorno model and is tackled numerically by Runge-Kutta 4th order procedure (RK4M) via a shooting scheme. The pictorial profiles were constituted to investigate the influence of physically parameterics on the major physical stream characteristics. The quantities of engineering interest are also presented graphically. Model predictions are compared against the results from the previously published study to confirm the precision and validity of the developed model. A relatively good agreement is achieved between benchmark value and model prediction. According to the observations the velocity slip factor boosts the temperature and concentration. Thermal slip declines the temperature profile near the wall. The non-linear stretched parameter escaltes the velocity and diminish the temperature. The temperature is a decreasing function of the heat source parameter.